A review of human milk oligosaccharide concentrations of breast milk for infants and young children through 24 months of age - Kenney, Adam D.; Sabag-Daigle, Anice; Stoecklein, Mary-Margaret; Buck, Rachael H.; Reverri, Elizabeth J. (Frontiers in Pediatrics, 2025)
The World Health Organization and American Academy of Pediatrics both support continued breastfeeding beyond 12 months of age up to 24 months of age or beyond. Human milk oligosaccharides (HMOs) are the third most abundant solid component in breast milk. HMO concentrations in early breast milk have been well-characterized, but less is known about HMO profiles later in lactation. The goals of this literature review and meta-analysis of studies that analyzed HMO concentrations at 12 months of lactation or beyond were to identify the most abundant HMOs in breast milk at various timepoints throughout lactation and assess dynamic changes in HMO concentrations over time. Literature searches were conducted to identify studies on HMO quantification following PRISMA guidelines. Only studies that measured HMOs at/beyond one year of age were analyzed. In total, thirteen studies met eligibility criteria. The identity and number of HMOs measured in each study were recorded. HMOs that appeared in at least 10 articles, termed herein as core HMOs, were selected for further analysis. Concentrations of these HMOs, as well as total HMO levels, were grouped by timepoint (colostrum, 6-, 12-, and >12-months). Core HMOs were identified as 2′-fucosyllactose (2′-FL), 3-fucosyllactose (3-FL), lacto-N-tetraose (LNT), lacto-N-neotetraose (LNnT), 3′-sialyllactose (3′-SL), and 6′-sialyllactose (6′-SL). These HMOs accounted for >70% of the total HMO pool across timepoints. Total HMO concentrations decreased from colostrum to 6-months but plateaued at 12-months through 24 months. Individual core HMOs generally followed the same trend, with the exception of 3-FL, which increased in concentration over time through 12 months. Overall, HMO concentrations remained at significant levels through one year and the relative abundance of the core HMOs throughout lactation suggests biological relevance. Several studies have demonstrated associations between HMO concentrations in infants with outcomes in young children. Extending these analyses to include prolonged consumption of HMOs (> one year) would be of general interest to the field. To the best of our knowledge, this review is the first to specifically synthesize studies that analyzed HMO concentrations at 12 months lactation. Further research may enhance the understanding of the effects of HMOs beyond infancy and into young childhood.